Tragedy and Resilience in Border Town Teasing Out Influence of Characters in Terms of Adversity, Fragility, and Strength of Human Spirit in the Face of Challenging Circumstances - Zhang, Youyou (Journal of Ecohumanism, 2024)
In this case, the critique focuses on tragedy and the spirit of the people in Shen Congwen’s novel Border Town. The nuts are released in a Chinese town where the primary focus is on individuals such as a little girl, Cuicui, and a grandfather who owns the ferry business. Through a focused discussion of the novel’s main characters and narrative arcs, this book offers a close and thorough examination of how the work captures the fine line between the explanatory power of vulnerability and the categorical imperative that is life. In other words, critique is the intersection of several schemes of literary theories and the relations between them in terms of contexts in their pluralism. Thus, adopting these theoretical frameworks, the work of the study demonstrates how the characters inhabit and navigate through reality. Cuicui, the main character, is depicted as an innocent and healthy girl who grows up, symbolizing every man’s journey through life when forced to bear loss and hardship. On the other hand, her grandfather represents aging and knowledge, accompanied by frailty, because his life's story is one of struggle and survival in a world fraught with hardship. Essential to this process is the understanding that "Border Town" is not just a story about countryside existence but something on the level of an existentialist parable. By creating complex and believable characters and their relationships, the novel reveals the layers of feelings and actions behind the concept of balancing. As such, this critique not only further enhances the appreciation of Shen Congwen as a literary artist but also constitutes a valuable addition to the discourse in literary studies in light of the continued significance of the concept of Resilience. In a nutshell, this study encourages the readers to explore the multiple layers of themes presented in "Border Town" beyond its chronological and geographical context. Overall, the critique proves that through careful reading, the novel has the potential to reveal the fundamental truths of human existence, fragility, and tenacity, as well as the pursuit of survival against all odds.